Perancangan Prototype Sistem Lampu Lalu Lintas Otomatis dengan Penjejakan Kendaraan Menggunakan Motion Detection-Blob dan Pengontrolan Berbasis Fuzzy Logic Control - Rahmad, Imam; Mirzal, Arisy; Berliyan, Alif Mahaputra (YASIN, 2023)
The purpose of this study is to describe the design of a prototype of an automatic traffic system with vehicle tracking using motion detection dlob and fuzzy logic control based control. Data collection techniques in this study used library research and laboratory research. The research was carried out by processing the data obtained by the author, data collection was carried out from March 2023. Based on the results and discussion it can be concluded that the calculation to obtain the traffic light signal time can be carried out by utilizing the Fuzzy Logic Toolbox found in Matlab computer program, and the performance generated by using Fuzzy logic theory has a smaller delay of 9.02 seconds. The duration of the green light generated by fuzzy logic corresponds to the volume of vehicles both in terms of vehicle arrivals and in terms of vehicle queues. The minimum value for the duration of the green light is 0 seconds and the maximum value is 15 seconds.